Development and Open Pilot Trial of an HIV-Prevention Intervention Integrating Mobile-Phone Technology for Male Sex Workers in Chennai, India. - Thomas, Beena; Closson, Elizabeth F; Biello, Katie; Menon, Sunil; Navakodi, Pandiaraja; Dhanalakshmi, A; Mayer, Kenneth H; Safren, Steven A; Mimiaga, Matthew J (Archives of sexual behavior, 2015)
In India men who have sex with men and engage in sex work (i.e., male sex workers; MSW) have a high risk of transmitting HIV. Globally, sex workers have become more spatially mobile due to advances in mobile-phone technology. In 2012 in-depth qualitative feedback was garnered from 40 interviews with MSW and four focus groups with 35 key informants (KIs) who had expert knowledge of the local MSW community to inform the design of an HIV-prevention intervention among MSW in Chennai, India. All MSW were recruited during outreach by employees of a Chennai-based organization for MSM (men who have sex with men). The data were analyzed using a descriptive qualitative approach. MSW and KIs discussed the need for intervention content that went beyond basic HIV psychoeducation. They emphasized the importance of addressing psychological distress, alcohol-related risk, and sexual communication skills. Concerns were raised about confidentiality, privacy, and scheduling. Participants endorsed a combination of in-person and mobile-phone-delivered sessions as well as the integration of mobile-phone messaging. These findings served as the basis for the development of a theoretically driven, manual-based intervention incorporating mobile phones. An open pilot assessed the feasibility and acceptability of the intervention with eight MSW. Assessments and HIV testing were administered at baseline, 3, and 6 months post-baseline. Exit interviews were conducted at the conclusion of the intervention. Retention for session attendance and assessment follow-up was 100 %. There was a high level of acceptability for the format, structure, and content. These data show initial promise, feasibility, and acceptability of the intervention.